(untitled) (Philology, 2026)
The paper outlines a system of Tones and Break Indices for Bulgarian (BG_ToBI) within the autosegmental-metrical framework of intonational phonology. While taking into account previous research on Bulgarian intonation, the system draws on more recent empirical research, and thus attempts to reflect the latest prosodic developments in the language. It is based on analyses of corpora specially collected for the purpose which include read as well as semi-spontaneous speech. We propose a system for transcription of Bulgarian intonation which comprises an inventory of two prosodic units (the intonation phrase and the intermediate phrase), five pitch accents (L∗, L∗+H, L+H∗, H∗, H+!H∗), two phrase accents (L− and H−) and three boundary tones (L%, H% and %H), and describe the default pre-nuclear and nuclear pitch accents and boundary tones for several communicative types of utterance. In order to account for the variable alignment of the default prenuclear pitch accent in Bulgarian, we propose another unit in the prosodic hierarchy which provides an anchorage domain for it—the prosodic word. Our analyses show that there are various strategies for signaling the information structure of an utterance by implementing different combinations of word order variation and intonational category choices. This research contributes to the study of Bulgarian intonation within the autosegmental-metrical model of intonational phonology, and of intonation grammar in general. However, more systematic research is needed on both the phonetics and phonology of intonation and the interplay of intonation, syntax and information structure in Bulgarian.